2012
DOI: 10.1074/jbc.m111.326553
|View full text |Cite
|
Sign up to set email alerts
|

Selective Gαi Subunits as Novel Direct Activators of Transient Receptor Potential Canonical (TRPC)4 and TRPC5 Channels

Abstract: Background: Activation of TRPC4/5 channels is mediated by GPCR activation. Results: TRPC4/5 was activated by the G␣ i/o -coupled receptor and the G␣ i protein, which interacted directly with each other. Conclusion: G␣ i proteins play an essential role as novel activators of TRPC4/5. Significance: Our findings provide new insights into the activation mechanism of inhibitory G␣ proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 44 publications
8
103
0
Order By: Relevance
“…4A, Right). These characteristics are known to be typical of TRPC channels (26). When cells were pretreated with leptin for 30 min, we observed a significant increase in the double-rectifying nonselective cation currents.…”
Section: Resultssupporting
confidence: 66%
“…4A, Right). These characteristics are known to be typical of TRPC channels (26). When cells were pretreated with leptin for 30 min, we observed a significant increase in the double-rectifying nonselective cation currents.…”
Section: Resultssupporting
confidence: 66%
“…(21,(24)(25)(26)(27)(28)32). To determine if IP 3 Rs are involved in TRPC4 activation, we applied the IP 3 R inhibitor heparin (3 mg/mL) by intracellular dialysis and found that most cells failed to respond to DAMGO and subsequent application of CCh (Fig. 3 A-C).…”
Section: Trpc4 Activation Requires Coincident G I/o Stimulation and Plcmentioning
confidence: 99%
“…In both heterologous and native systems, stimulating PLCβ via the G q/11 subgroup of G proteins is commonly used to activate TRPC channels. Recent studies, however, also suggest a role for G i/o subgroup of G proteins in the activation of TRPC4/C5 (2)(3)(4).…”
mentioning
confidence: 99%
“…1,2,13 . Related to Ga i protein, Rasd1 and homologs also activated TRPC4 by inducing GTP exchange for Ga i proteins.…”
Section: Discussionmentioning
confidence: 99%
“…1,13 Also, Rasd1 is functionally classified as a guanine nucleotide exchange factor (GEF) for Ga i proteins 46 and facilitates guanosine diphosphate (GDP) to GTP exchange of Ga i proteins and triggers it to be functionally active until intrinsic GTPase activity of Ga i protein turns off the signal by hydrolyzing GTP to GDP. Therefore, since the function of Rasd1 as a GEF of Ga i may resemble the activators of Ga i proteins, we expressed Rasd1 and mTRPC4b in HEK293 cells and detected the effect of Rasd1 on the activity of mTRPC4b.…”
Section: Trpc4 Channelsmentioning
confidence: 99%